COVID-19 in German competitive sports: protocol for a prospective multicenter cohort study (CoSmo-S) - Nieß, Andreas Michael; Widmann, Manuel; Gaidai, Roman; Gölz, Christian; Schubert, Isabel; Castillo, Katty; Sachs, Jan Philipp; Bizjak, Daniel; Vollrath, Shirin; Wimbauer, Fritz; Vogel, Azin; Keller, Karsten; et al. (International journal of public health, 2022)
Objective: It is unclear whether and to what extent COVID-19 infection poses health risks and a chronic impairment of performance in athletes. Identification of individual health risk is an important decision-making basis for managing the pandemic risk of infection with SARS-CoV-2 in sports and return to play (RTP). Methods: This study aims 1) to analyze the longitudinal rate of seroprevalence of SARS-CoV-2 in German athletes, 2) to assess health-related consequences in athletes infected with SARS-CoV-2, and 3) to reveal effects of the COVID-19 pandemic in general and of a cleared SARS-CoV-2 infection on exercise performance. CoSmo-S is a prospective observational multicenter study establishing two cohorts: 1) athletes diagnosed positive for COVID-19 (cohort 1) and 2) federal squad athletes who perform their annual sports medical preparticipation screening (cohort 2). Methods: Comprehensive diagnostics including physical examination, laboratory blood analyses and blood biobanking, resting and exercise electrocardiogram (ECG), echocardiography, spirometry and exercise testing added by questionnaires are conducted at baseline and follow-up. Results &Conclusion: We expect that the results obtained, will allow us to formulate recommendations regarding RTP on a more evidence-based level.
Gesehen am 11.04.2022